Partisipasi Masyarakat dalam Pengembangan Daya Tarik Wisata Tirta Empul di Desa Manukaya, Kecamatan Tampaksiring, Kabupaten Gianyar - Clara Fitra Yansani; Ida Bagus Gde Pujaastawa; Ida Ayu Alit Laksmiwati (Yayasan Literasi Sains Indonesia, 2024)
A tourism village is one kind of tourism that offers tourism potential owned by a village. Manukaya Village is one of the villages that had becoming a tourism village in Gianyar Regency, Bali. One of the concepts in the development of torist villages is comminity-based development which focuses on local community participation. Thus, it is to be expected that the benefits of tourism will be more for the local community as the legal owner of the resources. This study entitled “The Participation Community in the Development Tirta Empul Tourist Attraction in Manukaya Village, Tampaksiring District, Gianyar Regency” wich has aims to (1) explain the forms of community participation in developing the Tirta Empul Tourist Attraction and (2) explain the implications of developing the Tirta Empul Tourist b Attraction. This study uses a qualitative method. Data collection is done through observation, interview, literature review. The theory used to analyze the problem in this study is the theory of participation and the theory of tourism impact. The result of this study indicate that Manukaya Tourism Village has a tourism attarction. Local communities have a role in the planning, implementation, management, and evaluation processes in the development of tourism villages. Tourism activities in the Manukaya Tourism Village also have impacts that affect the community, such as economic aspects that improve the welfare of the local community, socio-cultural aspects that influence the sustainability of the Tirta Empul Temple and environmental aspects that influence the emergence of local community awareness to maintain the cleanliness of the Tirta Empul Temple environment.